2017
DOI: 10.1042/bio03904030
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species: rapid fire in inflammation

Abstract: Everyone has encountered it at some point: inflammation. That horrible feeling when you've hurt yourself and the skin and tissue around the injury swells, goes red, feels hot and painful. It is even worse if it gets infected, then you really know about it! You can feel sick, weak and feverish as your body tries to fight off the infection and heal itself. Inflammation is really important for keeping us healthy. Sometimes, however, the body's inflammatory response can be a bit overzealous, not shutting down when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…34,35 Likewise, ROS exert diverse pro-inflammatory effects. 36 Furthermore, our present findings indicate that both adipocytokines affect mRNA expression of various cytokines/chemokines. In particular, these factors up-regulate the mRNA level of IL-1b, TNF, and CCL3, which all, in different ways, promote the development of inflammation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…34,35 Likewise, ROS exert diverse pro-inflammatory effects. 36 Furthermore, our present findings indicate that both adipocytokines affect mRNA expression of various cytokines/chemokines. In particular, these factors up-regulate the mRNA level of IL-1b, TNF, and CCL3, which all, in different ways, promote the development of inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, cysLTs and chemokine CCL2 are factors that noticeably contribute to supporting and maintaining inflammatory responses, as they stimulate various cells to the production of pro‐inflammatory mediators, augment vascular permeability, enhance cell adhesion to the vascular epithelium, and may recruit immune cells into inflamed tissues . Likewise, ROS exert diverse pro‐inflammatory effects …”
Section: Discussionmentioning
confidence: 99%
“…In this particular study, the stimuli for the overexpression of this protein was the high ROS levels in semen of ROS+ men. In fact, there is a direct link between high ROS levels and inflammation [36]. A previous proteomic study also identified the overexpression of S100A9 in the seminal plasma of smoking men [37], which also reflects an environment with high ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of these changes can be useful for cell normal live or can lead to dysfunctions. This phenomenon is at the basis of almost all human diseases including communicable infectious diseases and non-communicable diseases such as Alzheimer, Parkinson, diabetes, autoimmune diseases and inflammatory diseases [2].…”
Section: Introduction mentioning
confidence: 99%